Achieving highly strength and stretchable deep eutectic iontronic elastomer by directly photopolymerizing HEA with ChCl. (16th January 2023) - Zhang, Dengfeng; Luo, Xu; Chen, Rong; Zhang, Minjie; Xiu, Fei; Dong, Xuemei; Li, Zifan; Zhang, Zicheng; Chen, Chen; Wang, Min; Liu, Juqing
Abstract: Deep eutectic ionic elastomers (DEIEs) as emerging iontronic conductors have shown great interest in flexible and wearable electronics. However, developing DEIEs with high strength and extreme stretchability remains challenging. In this paper, we report a facile strategy to prepare superior DEIEs by directly photopolymerizing HEA and ChCl. The synthetic elastomer exhibits high mechanical properties, with fracture strength of 0.804 MPa and fracture strain up to 1814%. Impressively, this elastomer can tolerate cutting and lift as high as 5 kg (7700 times its own weight) without failure. Moreover, the DEIEs also possess outstanding optical transparency (>90% in the visible range), desirable conductivity (2.47 × 10 −5  s cm −1 ), and excellent self-healing ability (electrical healing efficiency of 99.9% within 0.2 s). Using their strain-dependent iontronic resistance properties, versatile iontronic sensors for motion detection could be realized for human health care. Graphical abstract: Image 1 Highlights: Deep eutectic ionic elastomers (DEIEs) were prepared by photopolymerizing HEA and ChCl. The DEIEs exhibit high optical transparency, stretchability and fracture strength. The electric healing efficiency of DEIEs can reach 99.9%. The flexible DEIE-based sensor shows strain-dependent resistance properties with linearity. The obtained sensor could be used to monitor human movement for people health care.